PENGARUH PENAMBAHAN SARI JAHE (Zingiber officinale) TERHADAP KUALITAS ORGANOLEPTIK DAN DERAJAT KEASAMAN PADA TELUR PUYUH ASIN - Jejen Nurmila; Andri Kusmayadi; Putri Dian Wulansari (JURNAL SAINS PETERNAKAN NUSANTARA, 2023)
Eggs are a product produced from poultry which have high nutritional content but are easily damaged due to the egg's short shelf life. One alternative that can be done is processing eggs into salted eggs. Making salted eggs from ginger juice is expected to provide a distinctive taste, namely ginger, and improve the quality of salted eggs. The aim of the research was to determine the effect of adding ginger juice in terms of organoleptic quality and degree of acidity (pH). The ingredients used are quail eggs, ginger, salt and water. The research was carried out experimentally using a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments in this study were differences in the addition of 0% (P0), 30% (P1), 40% (P2) and 50% (P3) ginger juice. The results of the research showed that the addition of ginger juice had a significant effect (P<0.05) on the aroma and taste parameters of salted eggs, while the parameters of degree of acidity (pH), egg yolk color and saltiness had no significant effect (P>0.05). Providing ginger juice at the 40% level has a good effect on the quality of salted eggs compared to other levels. Keywords: ginger extract, organoleptic, pH, salted egg